Local molecular properties and their use in predicting reactivity - Ehresmann, Bernd; Martin, Bodo; Horn, Anselm; Clark, Timothy (Journal of Molecular Modeling, 2003)
Expressions for the local electron affinity, electronegativity and hardness are derived in analogy to the local ionization energy introduced by Sjoberg, Murray and Politzer. The local polarizability is also defined based on an additive atomic orbital polarizability model that uses Rivail's variational technique. The characteristics of these local properties at molecular surfaces and their relevance to electrophilic aromatic substitution, to S(N)2 reactivity and to the nucleophilicity of enolate ions are discussed.
Keywords: surface properties; AM1; local ionization energy; local electron affinity; local hardness